Basalt fiber-reinforced foam concrete containing silica fume: An experimental study - Gencel, Osman; Nodehi, Mehrab; Yavuz Bayraktar, Oguzhan; Kaplan, Gokhan; Benli, Ahmet; Gholampour, Aliakbar; Ozbakkaloglu, Togay (Elsevier BV, 2022)
Foam concrete refers to a type of low-density concrete that is commonly known to have favorable insulation and thermal performance due to its intentionally increased porosity. However, foam concrete is known to generally have a very low physico-mechanical and durability performance mainly due to its high porosity and the connectivity of the pores that can allow the entrance of unfavorable substances into the concrete medium. As a result, most often, foam concrete is considered inapplicable to major load bearing structural elements. To counter this tendency, this study adopted the use of basalt fibers with silica fume to increase the structural integrity of foam concrete. In that respect, 18 mixes with varying content of foaming agent, basalt fiber and silica fume have been prepared. Apparent porosity, water absorption, compressive, flexural and splitting tensile strength, sorptivity, ultrasonic pulse velocity (UPV), drying shrinkage, freeze-thaw, thermal conductivity, and thermal resistance tests were performed to evaluate the physico-mechanical, durability, and insulation properties of the produced foam concretes. Based on the results, a highly durable foam concrete with a maximum compressive, flexural and splitting tensile strength of ~ 46, 6.9 and 3.07 MPa, respectively, has been developed. Furthermore, it is observed that the inclusion of silica fume can significantly influence the pore network and enhance fiberpaste matrix. The effect of basalt fiber, however, is found to be more dependent on the use of silica fume, potentially due to its low integration with cementitious paste. The results of this study are significant and point out to the great potential for producing a highly durable and lightweight insulating foam concrete through the use of basalt fiber and silica fume.
Keywords: Basalt Fiber; Durability Of Foam Concrete; Foam Concrete; Silica Fume; Mechanical Properties; Thermal Conductivity; General Materials Science